Implementasi Sistem E-Tax Sebagai Moderasi Pengaruh Kepuasan Pengguna, Kualitas Informasi, Kualitas Sistem, dan Biaya Kepatuhan Terhadap Kepatuhan Perpajakan - Nazla Syafa Putri Rojani; Hasnawati (Economic Reviews Journal, 2024)
This study aims to examine the role of e-tax system implementation as a moderating variable in the relationship between taxpayer attitudes and tax compliance. This study involved 214 individual taxpayers who used the e-tax system, with the sampling technique using purposive sampling. The analysis method used is Structural Equation Modelling (SEM) which is processed using IBM SPSS AMOS 26 software. The results showed that the quality of the e-tax system has a positive effect on tax compliance, while compliance costs have a negative effect on tax compliance. In addition, the implementation of the e-tax system is proven to strengthen the effect of system quality on tax compliance, and weaken the effect of compliance costs on tax compliance. These findings indicate that improving the quality of the e-tax system and managing compliance costs can be effective strategies to improve tax compliance in the digital era.